The Efficacy of Solifenacin Added to Α-Adrenergic Antagonists in the Treatment of Lower Urinary Tract Symptoms in Males with Benign Prostate Hyperplasia (The Iraqi Experience) - AL-Hamdani, Nibbras I.; Daraji, Saad D.; Zeki, Ali W. (Journal of the Faculty of Medicine Baghdad, 2015)
symptoms/Benign prostate hyperplasia (LUTS/BPH) raises the possibility that a combination of α-adrenergic blocker therapy with anticholinergic therapy could both reduce the risk of retention or deteriorating bladder function and also add to the treatment of the remaining obstructive symptoms of LUTS/BPH.Objective: Is to investigate the efficacy and tolerability of 5mg solifenacin in the treatment of lower urinary tract symptoms in patients with benign prostatic hyperplasia in combination with an alpha-blocker.Patients and methods: This is a prospective study of 29 patients with benign prostatic hyperplasia already on alpha-blockers, given solifenacin 5mg once daily. International prostate symptom score (IPSS), patient micturition diaries, quality of life index (QOL), post-void residual urine (PVR) and maximum flow rate (Qmax) and urodynamic findings were recorded before and after three months of therapy. Adverse events were documented.Results: At baseline, the total IPSS was 15.3+5.7 that decreased to 10.8+5.3 (net change -4.5, P value